Coulomb Stress Change Analysis Center of Celebes on 29th May 2017 6.6 Mw Earthquake and Aftershocks Distribution - Ibrahim Ibrahim; Gazali Rachman; Bagus Jaya Santosa (IPTEK Journal of Proceedings Series, 2019)
Mechanism of earthquakes associated with the distribution of stress static that occurs in rocks. When the rocks elastic limit is exceeded there will be a release of energy as an earthquake result as rocks no longer able to withstand the stress that will disturb the stress field in the neighborhood. In this study, analysis stress of changes was done by taken earthquake data Center of Celebes 6.6 Mw on May 29th, 2017 with hypocenter 13 km using four earthquake recording stations namely BKB, TOLI, PMSI, and LUWI through website GFZ (Geo Forschungs Zentrum) and Global CMT (Global Centroid Moment Tensor), and then calculated the earthquake source parameters so as to obtain model focal mechanism using discretization methods are iterative wave numbers and analyzed using Coulomb 3.3 to obtain the value of Coulomb stress change and its aftershocks distribution. Analysis results showed that orientation the focal mechanism model of earthquake fault plane has been a normal fault type, fault length 27.54 km, width fault 14.06 km with slip shift of 79.06 cm. Coulomb stress Changes are generated ranging from 0.05 to 0.2 bar trending southwest-northwest and northeast-southeast of the epicenter, Based on Coulomb stress plot that center of Celebes 6.6 Mw on May  29,  2017 earthquake triggering aftershocks on May 29th, 2017 at 14:53:44 UTC with latitude and longitude -1.12 ° and 120.17 ° northwest trending with a range of values from 0.1 to 0.05 bar, on May 31, 2017 at 04:42:06 with latitude and longitude -1.17 ° and 120.79 ° north-east trending with a range of values from 0.15 to 0.1 bar and on November 25, 2017 at 09:14:51 UTC with latitude and longitude -1.18 ° and 119.93 ° and 11:11:24 UTC with latitude and longitude -1.19 ° and 119.94 westbound with a range of values from 0.05 to 0.01 bar